Cultural context of educational service management on example of e-learning website quality - Aleksandra Radziszewska (Journal of Modern Science)
Objectives The aim of this study is to examine how e-learning website features distinguish in cultural context and to propose the adaptation possibilities of the specific cultural characteristics in e-learning website design with regard to the influence of different cultural dimensions on quality perception.